The Role of Salivary Neuropeptides in Pediatrics: Potential Biomarkers for Integrated Therapies - Gershan, Lynn A (Eur J Integr Med, 2015)
INTRODUCTION: Objective measures of symptom response to integrated complementary approaches in pediatrics are evolving. The purpose of this study was to document the concentration range of salivary neuropeptides in healthy controls and in children with cancer, to explore correlations between serum and salivary measurements for Calcitonin Gene-Related Peptide (CGRP) and Vasoactive Intestinal Polypeptide (VIP), and to determine whether there is a change in these salivary neuropeptide levels in response to integrated mind-body therapies. METHODS: A non-randomized pragmatic study with three phases: Phase 1- Healthy Control Saliva-10 healthy controls provided saliva samples; Phase 2- Cancer Diagnosis Serum-Saliva- 16 mixed-type cancer patients provided blood and saliva samples; Phase 3- Acute Lymphocytic Leukemia (ALL) Saliva Intervention- 12 patients with ALL provided pre- and post-complementary intervention saliva samples. INTERVENTIONS: 20-minutes of structured touch or scripted relaxation breathing were administered to patients in Phase 3; Phase 1 and 2 patients did not receive this intervention. OUTCOME MEASURES: cortisol, CGRP, VIP, State/Trait Anxiety Scale, visual analogue scale, vital signs. RESULTS: Salivary CGRP and VIP were similar for children in Phases 1 and 2. There was a correlation between serum and salivary VIP in the mixed cancer group, though not between serum and salivary CGRP. In Phase 3 children, following a complementary intervention, salivary CGRP, heart rate, and systolic blood pressure decreased. DISCUSSION/CONCLUSIONS: These data provide evidence of a decrease in sympathetic output after integrative/complementary therapy intervention in children with cancer. The study underscores the potential role of salivary neuropeptides as non-invasive biomarkers for integrated therapies in pediatrics.